A Concept Analysis of the Properties and Conditions of Transformation - Ross, Susan L. (Advances in Social Sciences Research Journal, 2020)
Transformation is ceaselessly transpiring within and all around us. Despite its pervasive presence, the complex phenomenon remains fundamentally enigmatic. Previous work by this author indicates that existing literature about transformation tends to address its processes, antecedent conditions, catalyst, and/or outcomes. What is lacking is transdisciplinary understanding of the composition of transformation; that which causes transformation to exist. The purpose of this study is to draw upon literature across ten disciplines to discern properties and conditions integral to transformation. The method selected to achieve this aim is called concept analysis, which constitutes an empirical examination of a phenomenon described in literature, where a concept---transformation in this case---is the research object. The outcomes suggest a classification that indicates transformation is comprised of seven properties with five subproperties, three temporal conditions, and two contextual conditions. These findings constitute a unique contribution to social science research by identifying core aspects of transformation that transcend ethos typically applied in social sciences. Results offer opportunities to further establish a common language so that diverse disciplines can more precisely examine transformation, recognize and apply its processes towards individual and societal growth, and build upon existing theory.